Physical deployment of enhanced visible light communication system using forward error correction codes. (4th December 2019) - Khalid, Arslan; Rashid, Faizan; Muhammad Asif, Hafiz; Ali, Assad; Al‐Otaibi, Sattam
Summary: With the development of new generation lighting sources, visible light communication (VLC) system has become a complementary solution to traditional radio frequency wireless system. However, the error performance of VLC system is degraded because of multipath effects and interference from other lighting sources that, in turn, reduce the communication range. This work targets the issue of performance degradation of VLC systems in terms of communication range and demonstrates a VLC system design that utilizes forward error correction (FEC) codes as the main tool to fix this issue. Furthermore, the work also covers practical implementation of the proposed VLC system using UART modules programmed in MATLAB. The hardware results demonstrate that the communication range of the proposed VLC system is enhanced up to 0.5 m. Over and above, it is also shown through simulations that the coding gain of the proposed design is more when compared with existing VLC system(s). Abstract : An enhanced practically deployable indoor visible light communication (VLC) transceiver is designed and implemented using forward error correcting (FEC) codes. The main contribution of the work is to conceive a cost‐effective VLC testbed that can deliver variable transmission rates at different ranges. For physical implementation, the simulation packages are developed in such a manner that they can be modified to be interfaced with UART module. Both simulation and hardware results demonstrate the significant enhancement in VLC transceiver design. Through hardware experimentation, it is shown that if the range is the primary concern of VLC system, then BCH code with the low transmission rate can be the best suited option, while if VLC system requires high data rate communication, then we can employ BCH code with high transmission rate.